IMPACT OF CULTIVAR AND HARVEST TIME ON GROWTH, PRODUCTION AND ESSENTIAL OIL OF ANETHUM GRAVEOLENS CULTIVATED IN EGYPT - Hah, Said-al Ahl; Ea, Omer (International Journal of Pharmacy and Pharmaceutical Sciences, 2016)
Objective: The objective of this research was to compare growth and essential oil content and composition among eight dill cultivars harvested two times before the bolting of inflorescences. Methods: A two years field experiment was conducted on eight cultivars of dill in 2010/2011 and 2011/2012 seasons. Growth, herb fresh weight (g/plant) and essential oil content of the eight cultivars of dill were recorded at the first and second harvests after 60 and 90 d from sowing. The volatile oil content was analyzed by GC/MS. Results: Common cultivar was the best in plant height, the number of branches and fresh herb weight while Elephant cultivar was the best in the essential oil percentage. On the other, Compatto cultivar was least in plant height, the number of branches, fresh herb weight and essential oil %. The essential oil content was found to vary from 0.007-0.008% in the first harvest (harvest 60 d after sowing) and 0.042-0.045% in the second harvest (harvest 90 d after sowing). Anethum graveolens cv. Elephant was the highest in essential oil followed by cv. Bouquet, cv. Dukat and then cv. Common, cv. Tetra, cv. Vierling, cv. Local and finally cv. Compatto, which gave the lowest essential oil content. From the results of GC/MS obtained for the eight dill cultivars, six major compounds exist in eight cultivars, but with different percentages. Î±-phellandrene>limonene>dill apiol (Anethum graveolens cv. Local, cv. Compatto, cv. Common and cv. Bouquet); Î±-phellandrene>limonene>myristcin (Anethum graveolens cv. Tetra, cv. Vierling, cv. Dukat and cv. Elephant) were the major components in the first harvest (Î±-phellandrene chemotype). Î±-phellandrene>limonene>dill ether (Anethum graveolens cv. Local, cv. Tetra, cv. Vierling, cv. Ducat and cv. Common); Î±-phellandrene>limonene>p-cymene>dill ether (Anethum graveolens cv. Compatto, cv. Bouquet and cv. Elephant) were the major components in the second harvest(Î±-phellandrene and limonene chemotype). The second harvest gave the best values of growth, fresh herb weight and essential oil content as well as Î±-phellandrene, limonene, p-cymene and dill ether percentage in all cultivars than the first harvest. Except, myristcin which decreased in the European cultivars and increased in local cultivar in the second harvest than first one. Also, dillapiole increased only in Tetra cultivar in the second harvest and decreased in the other cultivars compared to the first harvest. Conclusion: The results obtained in this research clearly indicated superiority of European cultivars (Common, Bouquet, Elephant, Dukat, Vierling and Tetra, except Compatto cultivar) than the Egyptian cultivar (Local) in fresh herb weight (g/plant) and volatile oil content. Also, Common cultivar was more superior in growth characters, fresh herb weight (g/plant), essential oil content and the percentage of both Î±-phellandrene, limonene and dill ether. Elephant cultivar gave the lowest % of dill apiol (2.30-0.25%) in the first and second harvests, respectively. Keywords: Dill, Cultivar (cv.), Essential oil, Î±-phellandrene, Limonene, p-cymene, Dill ether, Dill apiol, Myristcin